ANALISIS PROGRAM PENGELOLAAN DANA ZAKAT DAN INFAK DALAM MEMBENTUK LINKING SOCIAL CAPITAL MASYARAKAT SEKITAR DI YAYASAN DANA SOSIAL AL-FALAH SUARABAYA - Gustin Listya Febriani Shaleh; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The aim of this research is to analyze zakat and infaq fund management program of  Yayasan Dana Sosial Al-Falah Surabaya in forming the surrounding community social capital linking. The research method used in this study is a descriptive qualitative approach with a case study method. Data collection is used with preliminary surveys, observations, interviews, and literature review. The research data was collected by interviewing six informants, including the Da'wah Program Manager, HR Manager, two YDSF Surabaya Mustahiks, and two YDSF Surabaya Muzakkis. The results show that the YDSF Surabaya zakat fund and infaq management program can shape social capital in the community. Programs that can shape social capital at YDSF Surabaya are da'wah programs and KUM programs.Keywords: Social Fund Foundation, Linking Social Capital, Zakat Fund And Infaq Management Program Yayasan Dana Sosial Al-Falah Surabaya, ZakatREFERENCESAl-Ba’ly, Abdul Al-Hamid Mahmud, 2006, Ekonomi Zakat, Jakarta: Raja Grafindo.Al-Faizin, Abdul Wahid dan Nashr Akbar, 2010. Tafsir Ekonomi Kontemporer. Jakarta: Madani Publishing House.Ali, Nuruddin Mhd. 2006. Zakat: Sebagai Instrumen Dalam Kebijakan Fiskal. Jakarta: PT. Raja Grafindo Persada.Beik, Irfan Syauqi. 2009. Analisis Peran Zakat dalam Mengurangi Kemiskinan: Studi Kasus Dompet Dhuafa Republika.Ghazaly, Abdul Rahman, Ghufron Ihsan, dan Sapiudin Shiddiq. 2010. Fiqh Muamalat. Jakarta: KencanaHafidhuddin, Didin. 2008. Panduan Praktis Tentang Zakat Infak Sedekah. Jakarta: GemaInsani.Hasan, M. Ali. 2006. Zakat dan Infak. Jakarta: KencanaHasbullah, J. 2006. Social capital (MenujuKeunggulanBudayaManusia Indonesia). Jakarta: MR-United PressKEMENAG., 2013. Panduan Zakat Praktis, KEMENAG, Jakarta.Qardhawi, Yusuf. 1999. Hukum Zakat. Bandung :Pustaka Mizan.Situs Resmihttps://www.bps.go.id/site/resultTab http://www.pusat.baznas.go.id